Semi-analytic AMR element model. (5th January 2018) - Teyber, R.; Trevizoli, P.V.; Christiaanse, T.V.; Govindappa, P.; Niknia, I.; Rowe, A.
Highlights: A framework is presented for analyzing multilayered active magnetic regenerators. The semi-analytic AMR element model is validated with multilayer performance data. A temperature span of 40 K is measured near a simulated optimum. Abstract: The active magnetic regenerator (AMR) cycle has the potential to reduce energy consumption and mitigate environmental pollutants. While layering regenerators with spatially varying Curie (or transition) temperatures has been shown to significantly increase AMR performance, layering strategies have yet to be developed. A central issue is the need for a modeling tool capable of efficiently screening the problems parameter space. A semi-analytic AMR element model is developed and validated with experiments over a broad range of operating conditions and regenerator compositions using second-order magnetocaloric materials. An optimization is performed and a temperature span of 40 K is measured in close proximity to the simulated optimum.